Looking to the future: the problematics of determining RE among early career teachers - Mogra, Imran (Journal of Religious Education, 2024)
The landscape of RE continues to evolve, in part, due to the academisation programme in England which is disrupting long-standing historical local structures. Following the National Plan by the Commission on RE, as a contribution to the ongoing debates, this study explores the perceptions of early career teachers about the future determination of RE. To examine such views, an online survey gathered quantitative data from PGCE and Year 3 students and a questionnaire gathered qualitative data from two groups in Year 1 of the BA Honours in Primary Education course at a university in the West Midlands, England. The findings are based on 149 survey responses and 52 completed questionnaires. This article reports the results about the membership and duties of Standing Advisory Council on Religious Education (SACRE) and the proposed Local Advisory Network for Religion and Worldviews (LANRW) from the Year 1 groups. The open-ended questionnaire data were analysed by thematic analysis. The results reveal that a small majority of the Year 1 groups were unhappy with the current membership setup of SACREs. However, a larger majority were happy with the current duties of SACREs. More than half of the responses received for the question about the creation of LANRWs agreed with this proposal. All responses received for the question about the representativeness of LANRWs agreed that the five groups proposed would make a LANRWs representative. A majority of the responses received for the question about the proposed roles designated for LANRWs also expressed their satisfaction with the roles. Based on these, further research is recommended.